Contribution and safety of the side‐to‐end hypoglossal‐to‐facial transfer in multidisciplinary facial reanimation. Issue 7 (4th May 2022) - Mato‐Patino, Teresa; Morales‐Puebla, José Manuel; Moraleda, Susana; Sánchez‐Cuadrado, Isabel; Calvino, Miryam; Gonzalez‐Otero, Teresa; Peñarrocha, Julio; Hernández, Borja; Gavilan, Javier; Lassaletta, Luis
Abstract: Background: This study evaluates facial and tongue function in patients undergoing side‐to‐end hypoglossal‐to‐facial transfer (HFT) with additional techniques. Methods: Thirty‐seven patients underwent a side‐to‐end HFT. Twelve had additional cross‐face grafts, and 9 had an additional masseter‐to‐facial transfer. Facial was assessed with House–Brackmann (HB), Sunnybrook Facial Grading Scale (SFGS), and eFACE. Martins scale and the Oral‐Pharyngeal Disability Index (OPDI) were used to assess tongue function. Results: Ninety‐four percent of cases reached HB grades III–IV. Mean total SFGS score improved from 16 ± 15 to 59 ± 11, while total eFACE score from 52 ± 13 to 80 ± 5. Dual nerve transfers were a predictor for a better eFACE total score p = 0.034, β = 2.350 [95% CI, 0.184–4.516]), as well as for a higher SFGS total score ( p = 0.036, β = 5.412 [95% CI, 0.375–10.449]). All patients had Martin's grade I. Mean postoperative OPDI scores were 84 ± 17 (local physical), 69 ± 16 (simple and sensory motor components), 82 ± 14 (complex functions), and 73 ± 22 (psychosocial). Conclusions: The side‐to‐end HFT offers predictable facial function outcome and preserves tongue function in nearly all cases. Dual nerve transfers appear to improve the final outcome.